KNOWLEDGE AND INFORMATION MANAGEMENT AS A FACTOR OF HIGHER EDUCATION QUALITY ASSURANCE AT UNIVERSITIES: FOREIGN EXPERIENCE - Нalyna Kalinicheva (Borys Grinchenko Kyiv Metropolitan University, 2021)
Today in a rapidly changing competitive environment each university faces the need to constantly transform the knowledge and information management system, to respond quickly, to predict and to apply new forms of change management that determine managerial innovations and their efficiency. Conceptual approaches and practical experience of the knowledge and information management system formation and functioning at a modern university have been studied in the article. The purpose of the article is to highlight the theoretical foundations of the knowledge management system formation and to compare the experience in organizing the process of knowledge and information management at leading foreign higher educational institutions. Based on the analysis of the models and the practical implementation of knowledge and information management, the author's vision of important components in the knowledge management system at modern educational institutions has been suggested. Taking into account the active use of the latest information and communication technologies in higher education systems of the majority of the world's countries, the importance of their application in the educational activities of participants in the educational process and in managerial activities of the administrative staff at universities has been stressed. This will optimize knowledge and information management at universities and will contribute to improving higher education quality, creating a competitive advantage in the market of educational services. The practical importance of knowledge and information management at university lies in the fact that the transfer of accumulated knowledge is aimed at the formation of competitive specialists, and in the fact that generation of new knowledge multiplies intellectual capital, provides competitive advantages and increases the competitiveness of the economy and society of any country.